Optical and Physical Properties of Methyltrimethoxysilane Transparent Film Incorporated with Nanoparticles - W. Ahliah Ismail; Zainal Abidin Ali; R. Puteh (Advances in Materials Science and Engineering)
Methyltrimethoxysilane has been used as a base in the formation of transparent sol-gel coatings on glass substrates. Several types of alcohol were used as solvents in order to obtain the highest transparency and scratch hardness of the film. The coating cures at room temperature (26∘C). The clarity of the coated film on the glass substrate was measured using haze meter. The best formulation based on the lowest haze values and light diffusion is the ratio of 1 : 1 trimethoxy silane to N-propanol. The haze value obtained for this system is 0.86, and the light diffusion was measured at 0.77%. Tack-free time and hardness were within acceptable value. Nanoparticles of silver, zinc oxide, and titanium dioxide were incorporated into the coating system from 0.5% to 2.5% by weight, and the haze values of the dried film were measured. The highest transparency was obtained from the samples that were mixed with 0.5% silver. The haze value for this sample is of 0.5.